2013
DOI: 10.1021/ef401880y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diluents and Asphaltenes on Interfacial Properties and Steam-Assisted Gravity Drainage Emulsion Stability: Interfacial Rheology and Wettability

Abstract: In steam-assisted gravity drainage (SAGD) operations, the produced fluids are complex water-in-oil-in-water (W/O/W) emulsions. A diluent is often added to reduce the density and viscosity of the heavy crude oil. However, the quality and composition of the diluents may in some cases increase emulsion stability and cause the dehydration of the oil to be more difficult because there are more surface-active agents added to the oil coming from the diluent streams. Thus, this work was aimed at studying the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
53
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 39 publications
7
53
0
1
Order By: Relevance
“…In a previous work we demonstrated that the interfacial oscillating drop tensiometer technique can be used to correlate the interfacial rheology of a diluted oil drop against brine with SAGD emulsion stability (Nguyen et al, 2014). Compressibility measurements showed that the aged interface between diluted oil and water behaves like a bidimensional gel near its gelation point, in agreement with other authors (Dicharry et al, 2006;Bouriat et al, 2004).…”
Section: Introductionsupporting
confidence: 88%
See 4 more Smart Citations
“…In a previous work we demonstrated that the interfacial oscillating drop tensiometer technique can be used to correlate the interfacial rheology of a diluted oil drop against brine with SAGD emulsion stability (Nguyen et al, 2014). Compressibility measurements showed that the aged interface between diluted oil and water behaves like a bidimensional gel near its gelation point, in agreement with other authors (Dicharry et al, 2006;Bouriat et al, 2004).…”
Section: Introductionsupporting
confidence: 88%
“…Theses values are lower than values of around 18 mN/m reported by other authors for Athabasca bitumens (Isaacs and Smolek, 1983). Since the brine used for this work has a very low salt concentration, most of the reduction is expected to be due to the presence of surface-active species in the diluents as has been reported previously (Nguyen et al 2014, Balsamo et al, 2013. The effect of temperature and pressure on crude oil interfacial tension is still not well understood.…”
Section: Untreated Emulsionsmentioning
confidence: 52%
See 3 more Smart Citations